BEKKER, Pieter Bailey Inventory of documents - BEKKER, Pieter Bailey (ARCA, 2017)
Private papers of P.B. Bekker, MPC Wakkerstroom [1943-1949], MP United Party Johannesburg North {1949-1954], National Conservative Party Johannesburg North [1954-1957], Independent [1957-1958].
COVERAGE 1953-1954; 1 File; 0,11 Metre.
Keywords: BEKKER, Pieter Bailey; Inventories; Politicians; National Party